Global Attractivity and Periodic Character of Difference Equation of Order Four - M. A. Obaid; E. M. Elsayed; M. M. El-Dessoky (Discrete Dynamics in Nature and Society)
We investigate the global convergence result, boundedness, and periodicity of solutions of the recursive sequence , where the parameters , andare positive real numbers and the initial conditions , and are positive real numbers.